The Multiscale TROPIcal CatchmentS critical zone observatory M‐TROPICS dataset II: Land use, hydrology and sediment production monitoring in Houay Pano, northern Lao PDR - Boithias, Laurie; Auda, Yves; Audry, Stéphane; Bricquet, Jean‐Pierre; Chanhphengxay, Alounsavath; Chaplot, Vincent; de Rouw, Anneke; Henry des Tureaux, Thierry; Huon, Sylvain; Janeau, Jean‐Louis; Latsachack, Keooudone; Le Troquer, Yann; et al. (Hydrological processes, 2021)
Mountain regions of the humid tropics are characterized by steep slopes and heavy rains. These regions are thus prone to both high surface runoff and soil erosion. In Southeast Asia, uplands are also subject to rapid land‐use change, predominantly as a result of increased population pressure and market forces. Since 1998, the Houay Pano site, located in northern Lao PDR (19.85°N 102.17°E) within the Mekong basin, aims at assessing the long‐term impact of the conversion of traditional slash‐and‐burn cultivation systems to commercial perennial monocultures such as teak tree plantations, on the catchment hydrological response and sediment yield. The instrumented site monitors hydro‐meteorological and soil loss parameters at both microplot (1 m2) and small catchment (0.6 km2) scales. The monitored catchment is part of the network of critical zone observatories named Multiscale TROPIcal CatchmentS (M‐TROPICS). The data shared by M‐TROPICS in Houay Pano are (1) rainfall, (2) air temperature, air relative humidity, wind speed, and global radiation, (3) catchment land use, (4) stream water level, suspended particulate matter, bed particulate matter and stones, (5) soil surface features, and (6) soil surface runoff and soil detachment. The dataset has already been used to interpret suspended particulate matter and bed particulate matter sources and dynamics, to assess the impact of land‐use change on catchment hydrology, soil erosion, and sediment yields, to understand bacteria fate and weed seed transport across the catchment, and to build catchment‐scale models focused on hydrology and water quality issues. The dataset may be further used to, for example, assess the role of headwater catchments in large tropical river basin hydrology, support the interpretation of new variables measured in the catchment (e.g., contaminants other than faecal bacteria), and assess the relative impacts of both climate and land‐use change on the catchment. Land use, hydrology and sediment production monitoring in Houay Pano, northern Lao PDR